2013
DOI: 10.5194/npg-20-883-2013
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolicity in temperature and flow fields during the formation of a Loop Current ring

Abstract: Abstract. Loop Current rings (LCRs) are among the largest mesoscale eddies in the world ocean. They arise when bulges formed by the Loop Current in the Gulf of Mexico close off. The LCR formation process may take several weeks, and there may be several separations and reattachments before final separation occurs. It is well established that this period is characterized by a persistent saddle point in the sea surface height field, as seen in both model and satellite data. We present here a detailed study of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…On the first day of our study, 11 June, the Loop Current is pinched off forming a large anticyclonic Loop as reported by Sulman et al (2013). Consistently, this scenario is observed both from AVISO and HYCOM data as observed from Fig.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…On the first day of our study, 11 June, the Loop Current is pinched off forming a large anticyclonic Loop as reported by Sulman et al (2013). Consistently, this scenario is observed both from AVISO and HYCOM data as observed from Fig.…”
supporting
confidence: 77%
“…A similar depth choice for this model is used, for instance, in Sulman et al (2013) or for CUPOM (Colorado University Princeton Ocean Model) in Branicki and Kirwan (2010). In the latter work the authors show how the resulting Lagrangian structure is close to 2-D surfaces that extend nearly vertically into the water column, thus confirming that the choice of a deeper layer just affects the noise on the observed structures.…”
Section: Hycomsupporting
confidence: 58%
See 2 more Smart Citations
“…Two-dimensional Lagrangian approach has been successfully applied for studying horizontal transport and mixing in numerically-generated and altimetric velocity fields in different basins, from bays (Lekien et al, 2005;Lipphardt et al, 2006;Gildor et al, 2009;Prants et al, 2013b) and seas (Abraham and Bowen, 2002;d'Ovidio et al, 2004;Schneider et al, 2005;Mancho et al, 2008;Prants et al, 2013a) to the ocean scale (Beron-Vera et al, 2008;Waugh and Abraham, 2008;Prants, 2013;Prants et al, 2014c). Lagrangian methods are especially suitable because they allow to delineate eddy's boundaries (Prants et al, 2011a;Beron-Vera et al, 2013;Prants et al, 2014c), to visualize transport barriers and corridors along which the core of an eddy is exchanged by water with its surrounding (Sulman et al, 2013;Prants et al, 2013b,a) and to quantify that transport (Miller et al, 1997).…”
Section: Introductionmentioning
confidence: 99%